Wave packet calculations on nonadiabatic effects for the O(3P)+HF(1?+) reaction under hyperthermal conditions - Gomez-Carrasco, S.; Bulut, N.; Banares, L.; Roncero, O. (Amer Inst Physics, 2012)
We present wave packet calculations of total and state-to-state reaction probabilities and integral cross sections for the nonadiabatic dynamics of the O(P-3)+HF -> F(P-2)+ OH((2)Pi) reaction at hyperthermal collision energies ranging from 1.2 to 2.4 eV. The validity of the centrifugal sudden approximation is discussed for the title reaction and a comprehensive investigation of the influence of nonadiabatic effects on the dynamics of this reactive system at high (hyperthermal) collision energies is presented. In general, nonadiabatic effects are negligible for averaged observables, such as total reaction probabilities and integral cross sections, but they are clearly observed in detailed observables such as rotationally state-resolved reaction probabilities. A critical discussion of nonadiabatic effects on the dynamics of the title reaction is carried out by comparing with the reverse reaction and the characteristics of the adiabatic and diabatic potential energy surfaces involved. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4753811]
Keywords: Potential-Energy Surface; H Plus Fo; Photodetachment Spectrum; Conical Intersections; Scattering Dynamics; Electronic States; Crossed-Beams; Oxygen-Atoms; Collisions; O(P-3)